2018
DOI: 10.3892/mmr.2018.8694
|View full text |Cite
|
Sign up to set email alerts
|

The mRNA, miRNA and lncRNA networks in hepatocellular carcinoma: An integrative transcriptomic analysis from Gene Expression Omnibus

Abstract: Research advances and analysis in the non-protein coding part of the human genome have suggested that microRNAs (miRNAs) and long noncoding RNAs (lncRNAs) are associated with tumor initiation, growth and metastasis. Accumulating studies have demonstrated that a class of miRNAs and lncRNAs are dysregulated in hepatocellular carcinoma (HCC) and closely associated with tumorigenesis, diagnosis and prognosis. In the present study, integrative analysis of published data on multi-level Gene Expression Omnibus (GEO) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The lncRNA expression pro les of HCC identi ed by microarray analysis have been previously reported (17,18). Zhu et al performed an lncRNA gene expression pro le analysis in 3 pairs of human HCC and adjacent non-tumor tissues using microarray containing 33,045 lncRNAs and 30,215 coding transcripts and identi ed 214 lncRNAs and 338 mRNAs abnormally expressed in all three HCC tissues with the genome-wide lncRNAs and mRNAs expression pro le analysis (17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lncRNA expression pro les of HCC identi ed by microarray analysis have been previously reported (17,18). Zhu et al performed an lncRNA gene expression pro le analysis in 3 pairs of human HCC and adjacent non-tumor tissues using microarray containing 33,045 lncRNAs and 30,215 coding transcripts and identi ed 214 lncRNAs and 338 mRNAs abnormally expressed in all three HCC tissues with the genome-wide lncRNAs and mRNAs expression pro le analysis (17).…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al performed an lncRNA gene expression pro le analysis in 3 pairs of human HCC and adjacent non-tumor tissues using microarray containing 33,045 lncRNAs and 30,215 coding transcripts and identi ed 214 lncRNAs and 338 mRNAs abnormally expressed in all three HCC tissues with the genome-wide lncRNAs and mRNAs expression pro le analysis (17). Additionally, Xu et al collected nine microarray expression data sets of mRNAs, miRNAs, and lncRNAs associated with HCC and found that 628 mRNAs, 15 miRNAs, and 49 lncRNAs were differentially expressed using integrative analysis (18). In our study, we analyzed lncRNA expression pro les of 125 HCCs with a custom microarray having a total of 2,412 lncRNA transcripts, which might signi cantly reduce the confounding factors caused by individual sample differences.…”
Section: Discussionmentioning
confidence: 99%
“…The RISC complex prevents the ribosome subunit from translating into a protein, so the gene is silenced. The tumorigenesis development can happen in the interaction between non-coding RNAs (lncRNAs), mRNAs and miRNAs [1] .…”
Section: Rna Biomarkersmentioning
confidence: 99%
“…Hepatocellular carcinoma (HCC) is considered as primary carcinoma in the liver, and the third vital carcinoma in the world after lung cancer and colorectal cancer. It was described as the fifth and seventh most common cancer in men and women, respectively [1]. HCC global distribution differs depending on the country, for example, African or Asian people, the HCC is considered as the most morbidity cancer into these countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation